2024
DOI: 10.7150/thno.89180
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte-to-macrophage communication exacerbate psoriasiform dermatitis via LRG1-enriched extracellular vesicles

Wenjuan Jiang,
Tingting Zhang,
Yueqi Qiu
et al.

Abstract: Rationale: Macrophage-associated inflammation and keratinocytes excessive proliferation and inflammatory cytokines secretion induced by stimulation play an important role in the progression of psoriasiform dermatitis. However, how these two types of cells communicate remains obscure. Methods:We induced a mouse model with experimental psoriasiform dermatitis by Imiquimod (IMQ). To investigate whether damaged keratinocytes promote macrophage polarization and accelerate skin lesions by releasing extracellular ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…This model reaction allowed researchers to conclude that the M1 phenotype of macrophages is promoted by high mobility group box-1 (HMGB1), a pro-inflammatory self-protein belonging to danger signals released by inflamed keratinocytes [53]. Moreover, an in vitro assay based on M5-treated HaCaT and THP-1 cell lines also suggested that M1 polarization is stimulated by crosstalk between keratinocytes and macrophages mediated by extracellular vesicles (EVs) [54]. Finally, keratinocyte ferroptosis was shown to promote macrophage M1 polarization [55].…”
Section: Polarization Of Macrophages In Psoriasismentioning
confidence: 99%
“…This model reaction allowed researchers to conclude that the M1 phenotype of macrophages is promoted by high mobility group box-1 (HMGB1), a pro-inflammatory self-protein belonging to danger signals released by inflamed keratinocytes [53]. Moreover, an in vitro assay based on M5-treated HaCaT and THP-1 cell lines also suggested that M1 polarization is stimulated by crosstalk between keratinocytes and macrophages mediated by extracellular vesicles (EVs) [54]. Finally, keratinocyte ferroptosis was shown to promote macrophage M1 polarization [55].…”
Section: Polarization Of Macrophages In Psoriasismentioning
confidence: 99%